Analysis of Student Active Learning in Moodle LMS Using the SERVQUAL Method: Analysis of Student Active Learning in Moodle LMS Using the SERVQUAL Method - Haidar Ali; Ucuk Darusalam; Agus Iskandar (Institute of Computer Science (IOCS), 2020)
Growth in the use of technology in education in Indonesia is increasing every year. Various universities in Indonesia already have e-learning systems based on LMS moodle. In the e-learning system, teachers and students generally do not meet face to face, so it is difficult to know how enthusiasm and response of students to the subject matter they receive and the success of the teaching and learning system itself. The purpose of this study is to design a system that can analyze the level of student activity. This system was created using PHP and mySQL programming languages as a database and data analysis with the SERVQUAL method. Based on the results of research analysis of learning by using the best ranking servqual method, namely students named Vony Oktavia (193112700650077) with the highest weighting value of 1.57143 out of 30 students.